Selective Control of Polyamide Dyeing with Acid Dyes Using Hydroxypropyl-β-cyclodextrin - Santos, Jorge (2014)
e effect of hydroxypropyl-β-cyclodextrin (HPβCD) in the dyeing of polyamide fabric was investigated under conditions that mimic industrial dyebaths where dye mixtures are used. The dyes used were Telon Red BN, Telon Yellow A-2R, and Telon Blue RR. The blue dye complexed with HPβCD whereas the other dyes did not do so under the conditions used. The dyeing results were compared with those obtained using a traditional retarding agent, Albegal B. The exhaustion dyeing data showed that HPβCD mainly affected the dyeing behavior of the blue dye that became encapsulated. In the case of the yellow and red dyes, changes in the overall kinetics of dyeing were observed, resulting in modified exhaustion profiles. In comparison, Albegal B retarded the blue dyeing process and increased the rate of exhaustion of the yellow dye while the exhaustion curve of red dye remained unchanged. The color uniformity of the dyed polyamide was improved when HPβCD was used. This resulted from the more controlled exhaustion rate during the critical phase of the dyeing process.